Especies nuevas de abejas de Cuba y La Española (Hymenoptera: Colletidae, Megachilidae, Apidae) - Genaro, Julio A (2001)
Five new species of Antillean bees are described and illustrated: Colletes granpiedrensis n. sp. (Cuba) (Colletidae) is charaterized as follows: Head and mesosoma black, legs and metasoma brown. Dense brown hairs on head and mesosoma; white on frons and metasomal terga. Clypeus, frons and mesosoma with large punctures, lesser on vertex and metasoma. Malar space more wide than long. Male and female slightly similar, except in the apical margin of clypeus, supraclipeal area, and color of the pubescence on legs and sterna; Osmia (Diceratosmia) stangei n. sp. (Dominican Republic) (Megachilidae) is charaterized as follows: Dark metallic green, metasoma black with metallic green reflections. Pubescence light; body with large, closed punctures. Female with violet reflections in tergum III and mandible tridentate; Coelioxys (Cyrtocoelioxys) alayoi n. sp. (Cuba) (Megachilidae) is charaterized as follows: Female black, except basal area of mandibles, tegula, legs, lateral area of tergum I and sterna, reddish brown. Posterior margin of scutellum rounded. Apex of tergum VI with spine curved up. Sternum VI fringed with short, closed setae, and the apex with short spine; Coelioxys (Boreocoelioxys) sannicolarensis n. sp. (Cuba) (Megachilidae) is charaterized as follows: Black, except antenna and tegula brown; legs and sterna reddish brown. Clypeal margin straight in profile. Gradular grooves on metasomal terga II and III distinct medially. Fovea on metasomal tergum II of male deep and short, and Triepeolus nisibonensis n. sp. (Dominican Republic) (Apidae) is charaterized as follows: Dorsal pubescence (short and dense) on mesosoma and metasoma from white to yellow, according to specimen; ventral pubescence white. Tergal bands of hairs interrupted medially; two spots of light pubescence on tergum II. Male metasomal sternum VII with anterior margin V-shaped and basal constriction narrow.